Harnessing New Pedagogy: Transforming the Learners in the Twenty-First-Century - Regmi, Bhim Nath (Curriculum Development Journal, 2024)
This article explores the use of e-teaching-learning in higher education. It focuses on its benefits in classrooms enhancing communication to adapt its curricula, goals, and pedagogies to meet the needs of twenty-first-century learners. It proposes the e-teacher subsystem and blended teaching model as a crucial component of an integrated teaching system to change thinking and learning behavior. The research gathers facts from primary and secondary data. 25 students from NOU and TU were selected, and 5 faculties from the same universities were interviewed. Phenomenography is a qualitative research approach that emphasizes content oriented explanation and utilizes a qualitative interpretive approach, which has limitations in generalizability to Nepali higher education due to subjectivity and small sample size but has enhanced validity and trustworthiness. The theory consists of two levels: macro-level decentralization and diversification, internationalization and digital technologies, and micro-level teacher-learner relationships combining traditional and innovative methods. The use of new pedagogy is crucial for teachers to improve students’ achievement, and it should be revisited to maximize educational objectives. Adapting technology, differentiated instruction, and student-centered approaches is essential. The global movement for a new learning model for the twenty f irst century calls for transforming formal education to address complex global challenges. Experts recognize that the transmission or lecture model is ineffective for teaching twenty-first-century competencies, and critical thinking, communication, innovation, and problem-solving are useful to transform the learners.